2021
DOI: 10.1111/1462-2920.15882
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic niche differentiation of novel sediment ecotypes of Ruegeria pomeroyi correlates with nitrate respiration

Abstract: Marine intertidal sediments fluctuate in redox conditions and nutrient availability, and they are also known as an important sink of nitrogen mainly through denitrification, yet how denitrifying bacteria adapt to this dynamic habitat remains largely untapped. Here, we investigated novel intertidal benthic ecotypes of the model pelagic marine bacterium Ruegeria pomeroyi DSS-3 with a population genomic approach. While differing by only 1.3% at the 16S rRNA gene level, members of the intertidal benthic ecotypes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 77 publications
1
7
0
Order By: Relevance
“…In sediment, abundant OTUs were assigned to the genera Ruegeria (family Rhodeobacteraceae), Methyloceanibacter (family Methyloligellaceae) and Filomicrobium (family Hyphomicrobiaceae). Members of these families were previously found to be abundant in marine sediment and are known to play an important role in nutrient remineralization (Begmatov et al, 2021; Dong et al, 2022; Lin et al, 2022; Vekeman et al, 2016). Recently, Ruegeria strains isolated from marine sediment were observed to utilize various organic and inorganic compounds, oxidize sulfur, and perform complete denitrification by reducing nitrate to molecular nitrogen (Lin et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In sediment, abundant OTUs were assigned to the genera Ruegeria (family Rhodeobacteraceae), Methyloceanibacter (family Methyloligellaceae) and Filomicrobium (family Hyphomicrobiaceae). Members of these families were previously found to be abundant in marine sediment and are known to play an important role in nutrient remineralization (Begmatov et al, 2021; Dong et al, 2022; Lin et al, 2022; Vekeman et al, 2016). Recently, Ruegeria strains isolated from marine sediment were observed to utilize various organic and inorganic compounds, oxidize sulfur, and perform complete denitrification by reducing nitrate to molecular nitrogen (Lin et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Members of these families were previously found to be abundant in marine sediment and are known to play an important role in nutrient remineralization (Begmatov et al, 2021; Dong et al, 2022; Lin et al, 2022; Vekeman et al, 2016). Recently, Ruegeria strains isolated from marine sediment were observed to utilize various organic and inorganic compounds, oxidize sulfur, and perform complete denitrification by reducing nitrate to molecular nitrogen (Lin et al, 2022). The Methyloligellaceae and Hyphomicrobiaceae families include bacterial species, which are able to reduce one-carbon compounds (methylotrophs) and oxidize methane under aerobic conditions (Vekeman et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Ruegeria was the dominant genus in the total, napA, and nosZ bacterial communities which is rarely reported and used in applications. Ruegeria is a common denitrifier carrying a complete gene set for denitrification in coastal environments (Lin et al, 2022;Meng et al, 2022). Therefore, future applications of denitrifying bacteria may target the isolation of the Ruegeria geneus.…”
Section: Bacterial Community Composition and Dynamic Patternmentioning
confidence: 99%
“…We further found that Maribacter and Ruegeria were dominant taxa present in both the total bacterial community and the nosZ denitrifiers in the co-occurrence network (Supplementary Figure S13). This could be attributed to the high salinity tolerance and robust denitrification capabilities of Maribacter and Ruegeria in saline conditions (Li et al, 2013;Lin et al, 2022). Moreover, Maribacter is known to utilize lipid compounds, a primary ingredient in formulated feed, and its secondary metabolites may benefit denitrifers (Bonin et al, 2015).…”
Section: Microbial Co-occurrence Network Of Denitrifying Bacteriamentioning
confidence: 99%
“…For bacteria inhabiting marine environments, the use of this population genomics approach is in its infancy. It has been largely applied to lineages with large and variable genomes, such as the Vibrio ( 9 , 12 , 13 ) and Ruegeria lineages ( 14 16 ), that readily grow on solid media. In sunlit pelagic oceans, however, a typical bacterioplankton cell often carries a reduced genome (with an average genome size of 2.2 to 2.6 Mbp) ( 17 ).…”
Section: Introductionmentioning
confidence: 99%